New Naticidae (Mollusca: Gastropoda) from Brazil - Santos Costa, Paulo Mauricio (2012)
Two new species are described from Brazil. Notocochlis laurae n. sp. from the Canopus Bank, a seamount located 160 Km off Fortaleza, Ceará, is characterized by its large size, the umbilical and parietal calluses separated by a notch; a straight sulcus, and a moderately developed funicle. Color brownish white, with axial and oblique bands extending from the suture to the lower third of the whorl; the subsutural region with a thin white spiral band. N. isabelleana, a shallow water species, is comparable and can be differentiated from N. laurae by its small size, rounded shape, coloration pattern and operculum with only one marginal rib. Notocochlis guesti a deep water species that occurs in Bermuda Is. and the Caribbean can be differentiated by its rounded profile, pale coloration pattern and some radular characters. Natica juani n. sp., distributed from southern Brazil to Uruguay, has a small, smooth shell, with an obsolete funicle. The shell color pattern has axial brownish zig-zag, interconnected, flammules over a white background. The internal margin of the operculum is serrate and the external margin has two thick cords. It is similar to N. perlineata and N. menkeana both Caribbean species with different coloration pattern and a thicker funicle in the latter.